The use of Information and Communication Technology (ICT) in teaching and learning of Language - Eneremadu Queen Esather; Ndubuaku Rosita Amam (MultiTech Publisher, 2024)
The use of Information and Communication Technology (ICT) in teaching and learning of Language has been extensive. It has been effective in increasing performance and retention rate. Research has shown that people remember 20% of what they see, 40% of what they see and hear, but about 75% of what they see, hear and do simultaneously (Lindstrom 73). ICT is now permeating the educational system as a tool for effective teaching and learning. With multimedia, the communication of information can be done in a more effective manner and it can be effective instructional medium for delivering information. Multimedia access to knowledge of the possibilities of information and communication technology has tremendous impact on learning. The instructional media have emerged in a variety of resources and equipment, which can be used to supplement or complement the teacher’s efforts in ensuring effective learning by students. It is recognized that conventional media technologies can no longer meet the need of our teaching and learning process; as a result, they are being replaced by multimedia technology.